The Risk Level of Type 2 Diabetes Mellitus in University Students: A Descriptive Study - Sinta Wati, Diana; Sugiyo, Dianita; Haris, Fahni (Jurnal Ilmiah Kesehatan, 2025)
University students are vulnerable to sedentary lifestyles, characterised by poor diet and minimal physical activity, which increase the risk of type 2 diabetes mellitus (T2DM). Early detection is essential to reduce the prevalence of T2DM among young individuals. This study aimed to assess the risk levels of T2DM among university students using the FINDRISC-BI screening tool and analysed the distribution of risk levels—low, slightly increased, moderate, and high—along with contributing factors. A descriptive quantitative method with a cross-sectional design was utilised, conducted in March 2025. A total of 251 respondents participated using a convenience-cluster sampling technique. The study found 64.1% of participants at low risk, 25.1% at slightly increased risk, 6.8% at moderate risk, and 4.0% at high risk of T2DM. Many students showed inadequate physical activity and lacked daily consumption of vegetables and fruits. In conclusion, while most students were at low risk, a significant portion exhibited elevated risk levels, highlighting the need for further medical assessment and preventive strategies.